Self-Paced Endurance Performance and Cerebral Hemodynamics of the Prefrontal Cortex: A Scoping Review of Methodology and Findings. Issue 4 (August 2022) - Hyland-Monks, Robert; Marchant, David; Cronin, Lorcan
Recent research has suggested that top-down executive function associated with the prefrontal cortex is key to the decision-making processes and pacing of endurance performance. A small but growing body of literature has investigated the neurological underpinnings of these processes by subjecting the prefrontal cortex to functional near-infrared spectroscopy (fNIRS) measurement during self-paced endurance task performance. Given that fNIRS measurement for these purposes is a relatively recent development, the principal aim of this review was to assess the methodological rigor and findings of this body of research. We performed a systematic literature search to collate research assessing prefrontal cortex oxygenation via fNIRS during self-paced endurance performance. A total of 17 studies met the criteria for inclusion. We then extracted information concerning the methodology and findings from the studies reviewed. Promisingly, most of the reviewed studies reported having adopted commonplace and feasible best practice guidelines. However, a lack of adherence to these guidelines was evident in some areas. For instance, there was little evidence of measures to tackle and remove artifacts from data. Lastly, the reviewed studies provide insight into the significance of cerebral oxygenation to endurance performance and the role of the prefrontal cortex in pacing behavior. Therefore, future research that better follows the guidelines presented will help advance our understanding of the role of the brain in endurance performance and aid in the development of techniques to improve or maintain prefrontal cortex (PFC) oxygenation to help bolster endurance performance.